2021
DOI: 10.1111/raq.12614
|View full text |Cite
|
Sign up to set email alerts
|

On the silver jubilee of crustacean antimicrobial peptides

Abstract: Antimicrobial peptides (AMPs) are widely distributed effector molecules that provide a first line of defence for organisms that lack adaptive immunity, such as crustaceans.They also represent bioactive molecules with great potential as therapeutic agents in aquaculture and biomedicine. Over the last years, an intensive research effort has been devoted to the identification and characterisation of antimicrobials in crustaceans resulting in the recognition of twelve gene-encoded AMP families to date. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 177 publications
0
25
0
Order By: Relevance
“…AMPs and melanisation are the two most powerful shrimp humoral responses. Intensive studies have demonstrated a close link between the proPO activation cascade and the AMP synthesis pathway via pattern recognition protein crosstalk in shrimp, which enables the innate immune system to execute an effective immune response ( 22 , 23 ). Molecular processes such as peptidase activity and peptidase inhibitor activity are significantly enriched in Hem4, molecular processes related to cellular activities, such as chromosome organization and DNA replication are enriched in Hem6; cytoskeleton organization and apoptosis are enriched in Hem7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPs and melanisation are the two most powerful shrimp humoral responses. Intensive studies have demonstrated a close link between the proPO activation cascade and the AMP synthesis pathway via pattern recognition protein crosstalk in shrimp, which enables the innate immune system to execute an effective immune response ( 22 , 23 ). Molecular processes such as peptidase activity and peptidase inhibitor activity are significantly enriched in Hem4, molecular processes related to cellular activities, such as chromosome organization and DNA replication are enriched in Hem6; cytoskeleton organization and apoptosis are enriched in Hem7.…”
Section: Discussionmentioning
confidence: 99%
“…Monocle2 analysis showed that the expression levels of AMPs and GSH-Px showed different or even opposite trends at the developmental endpoints of haemocytes with different fates. In several invertebrates, AMPs are used as indicator genes for cell classification and cell state ( 4 , 22 ). This finding may also suggest that AMPs and GSH-Px play important roles in cell differentiation and functional plasticity of shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of bioactive peptides is reflected in several reviews on AMPs in mammals [ 19 ], amphibians [ 20 ], fishes [ 21 ], plants [ 22 ], insects [ 23 ], echinoderms [ 24 ], marine arthropods [ 16 , 25 , 26 ], and penaeid shrimps [ 27 , 28 ]. Remarkable research has been conducted in this area [ 29 ]; therefore, our review emphasizes the synthetic chemistry of AMPs and their tentative medicinal applications. We describe recent advances regarding the molecular analysis of crustacean AMPs, concentrating on the antimicrobial mechanisms of these molecules against most pathogens in aquatic arthropods.…”
Section: Introductionmentioning
confidence: 99%
“…AMPs produced by the innate immunity in crustaceans present some novel drug properties. As reviewed by Matos and Rosa [ 17 ], ALF-derived peptides are diverse bioactive molecules, modulating inflammatory responses and displaying activity against human parasites, viruses and tumors. Some PENs can behave as cytokines attracting hemocytes towards sites of injury and bind to chitin, suggesting a role in wound healing.…”
Section: Introductionmentioning
confidence: 99%